Nikah Beda Agama dalam Kajian Hukum Islam dan Tatanan Hukum Nasional - Muhammad Ilham (Universitas Islam Negeri Sumatera Utara, 2020)
Legitimate marriage is a dream for couples and harmony in family life, so that in Islam always depends on the ultimate goal Marriage is to get sakinah, mawaddah and warohmah. With this aim, sometimes it is wrong to place the rules of marriage only, one of them agreeing on a harmonious family but forgetting to look at the couple's religious side. The phenomenon of interfaith marriages often occurs not only in different countries but also in Indonesia, a lot of this is done.This study aims to look at the phenomenon of interfaith marriage in a qualitative form so that the ultimate goal can be developed with special concepts to be given at specific conclusions with various updates.Interfaith marriages often occur in Indonesian society, in marriage law No. 1 of 1974 concerning marriage clearly has a ban. Also in the Compilation of Islamic Law in Article 40 paragraph (c) and Article 44, too. The same can also be seen in the MUI Fatwa. Nevertheless, there are also some opinions of scholars who allow marriages of different religions from Muslim men and women experts of the book. In response, it is fitting to look at the social conditions of people in Indonesia who uphold religious norms, so that depending on the committee will be corrected on the understanding of specific ideas in matters of religion